1983
DOI: 10.1016/s0735-1097(83)80195-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whiskey on atrial vulnerability and “holiday heart”

Abstract: Vulnerability to atrial fibrillation and flutter was examined in 11 alcohol abusers who did not have cardiomyopathy or manifest heart failure. Atrial extrastimulation was done with rapid pacing (drive cycle length 500 ms) to facilitate induction of atrial vulnerability, seen in four alcohol abusers. The remaining seven were retested 30 minutes after drinking 60 to 120 ml of 86 proof whiskey (ethanol blood levels were 49 to 101 mg/100 ml but pulmonary capillary wedge pressure remained normal in all) and atrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Nevertheless Ettinger et al 14 also describe the case of a healthy non-regular drinker who presented with AF after alcohol consumption, hinting that HHS could also occur in this group of subjects. This was later confirmed by other studies showing similar cases of sudden onset of cardiac arrhythmias after heavy drinking in non-alcoholic healthy people 7,16 . …”
Section: Methodssupporting
confidence: 77%
“…Nevertheless Ettinger et al 14 also describe the case of a healthy non-regular drinker who presented with AF after alcohol consumption, hinting that HHS could also occur in this group of subjects. This was later confirmed by other studies showing similar cases of sudden onset of cardiac arrhythmias after heavy drinking in non-alcoholic healthy people 7,16 . …”
Section: Methodssupporting
confidence: 77%
“…[17], [18] Several pathologic mechanisms and electrophysiologic changes of the underlying cardiac substrate have been described. [19]- [25] Furthermore, chronic alcohol can be associated with other traditional risk factors, such as hypertension, and promote atrial fibrosis and subsequently AF. [26] Conflicting Evidence Regarding Alcohol Consumption and Atrial Fibrillation Several studies have shown a deleterious relationship between the increased daily amount of consumed alcohol and the incidence of AF.…”
Section: Alcohol Consumption and Risk Of Atrial Fibrillationmentioning
confidence: 99%
“…Patients (especially men) admitted for idiopathic atrial fibrillation have been shown to have consumed more alcohol during the week preceding their admission than either control patients4 or the population outside hospital.5 In one study 60% ofpatients with idiopathic atrial fibrillation coming on at the weekend were problem drinkers, according to the CAGE questionnaire,9 compared with only 12% in the community."' The association of alcohol with other types of supraventricular tachyarrhythmias is less clear," but in the Kaiser Permanente study people consuming more than six drinks a day had a higher risk of all supraventricular tachyarrhythmias than people matched for age, sex, race, and smoking but consuming less than one drink a day.6 Finally, alcohol has occasionally also been shown to promote the onset of ventricular tachyarrhythmias.i 8 How might alcohol promote arrhythmias? Subclinical alcoholic disease of the heart muscle may contribute by producing patchy delays in conduction, and potassium and magnesium depletion may also be factors,' as may the hyperadrenergic state accompanying alcohol withdrawal.…”
Section: Alcohol and Cardiac Arrhythmiasmentioning
confidence: 99%
“…These complications occurred, respectively, in 6% and 4% of patients. 8 The main indication for enteral nutrition is difficulty in swallowing in patients with neurological disease. Pulmonary aspiration is a serious hazard for those who are unable to protect their airway, yet it is precisely these patients in whom some form of nutrition must be established.…”
Section: Alcohol and Cardiac Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation